Tetanus vaccination status in construction workers: results from an institutional surveillance campaign - Riccò, Matteo; Vezzosi, Luigi; Cella, Carlo; Pecoraro, Marco; Novembre, Giacomo; Moreo, Alessandro; Ognibeni, Enrico Maria; Schallenberg, Gert; Maranelli, Graziano (Acta Biomedica Atenei Parmensis, 2019)
Background: Since 1963 Italian law (Law 292/1963, Legislative Decree n.81/2008), defines Tetanus Vaccination (TeV) as mandatory for defined occupational categories, including Construction Workers (CWs). Materials and Methods: An institutional survey on of CWs was performed in the Autonomous Province of Trento (Oct. 2016 - Apr. 2017). Vaccination booklets/certificate were retrieved recalling: TeV status (1), and TeV settings (2), i.e. basal schedule; year of last shot, healthcare providers who performed TeV, and TeV formulate(s). Results: Data about 205 CWs were collected (mean age 40.6±10.3 years; 78.0% 10 years before the survey (mean: 8.8 ± 8.2 years). The majority of boosters had been administered by Vaccination Services of the Local Health Unit (47.3%), followed by Occupational Physicians (20.0%) and General Practitioners (11.2%). In 85.9% of CWs, a monovalent formulation was used. Combined TeV were mainly reported in CW who had received last vaccination shot in Vaccination Services (96.2%; p